GAMBARAN AHMAD DAHLAN DAN WAHAB HASBULLAH DALAM PENDIDIKAN ISLAM TERHADAP NASIONALISME INDONESIA - Setiawan, Satria; Sujati, Budi (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2019)
ABSTRACTThis paper will describe a problem concerning Islamic education in Indonesia which is still underestimated. This is very much related to the history of the Indonesian nation which had been colonized for centuries by the Dutch. Therefore, the Islamic community is disadvantaged by the rampant terrorist terrorism, and the severity of this terrorist is associated with Islam, because in practice it always carries Islamic symbols. This has an impact on the assessment of some people who say that Islamic society (santri, kiai, pesantren) do not have a spirit of nationalism. Whereas if we look at history, that Islamic society has a very big contribution to Indonesian independence, we know with the resistance made by Prince Diponegoro which ended with the Diponegoro war, as well as with other resistance carried out by Islamic communities throughout Indonesia. This illustrates how deep the sense of nationalism is owned by the Islamic community. Efforts to counter the notion that the Islamic community does not have a spirit of nationalism is to study the characters, although briefly. With Ahmad Dahlan and Abdul Wahab Khasbullah taken as a presentation of this paper.Â Keywords : Influence, Islam, Nationalism.